Pengaruh Pemberian Nitrogen dan Boron Melalui Daun terhadap Mutu Benih Kedelai (Glycine max (L.) Merril ) - Julita HD; Syamsuddin Syamsuddin; Rita Hayati (Jurnal Floratek, 2016)
Effect of Foliar Application of Nitrogen and Boron on Quality of Soybean Seed (Glycine max (L.) Merril)ABSTRACT. The aim of this research was to investigate the effect of foliar application of nitrogen and boron on quality of soybean seed (Glycine max (L.) Merril). The research was conducted at Balai Pengkajian Teknologi Pertanian (BPTP) Aceh, Seed Laboratory of Agriculture Faculty, Syiah Kuala University and Center for Biological Resources and Biotechnology, Institute for Research and Community Empowerment, Bogor Agricultural Institute which is started from June 2013 to February 2014. This research was carried experimentally using a randomized block design with three replication, consist of two factor. The first factor was nitrogen concentration witch consisted of four levels: 0, 0,2, 0,4 and 0,6%. The second factor was boron dossages ie : 0, 0,35, 0,45, 0,55 kg B ha-1. The results showed that nitrogen concentration have very significant effect on germination, the rate of seed growth, seed growth simultaneity and significant effect on seed protein content. Best nitrogen concentration level found in the use of 0,6% N. Boron have very significant effect on germination, seed growth simultaneity and significantly effect on the rate of seed growth. The best boron level was found at a dose of 0,45 kg B ha-1. The combination of boron 0,6% N and 0% gives a higher yield for the germination, the rate of the seed growth, seed growth simultaneity and protein, which is not significantly different from its value with the addition of boron 0,35, 0,45 and 0,55 kg B ha-1.